Regional Concentration and Specialisation in Agricultural Activities in EU-9 Regions (1950-2000) - van Leeuwen, Eveline S.; Strijker, Dirk; Terluin, Ida J. (European Spatial Research and Policy, 2010)
Both traditional (von Thünen) and modern (Hayami & Ruttan, Krugman) theories on land use suggest that productions with a high value added per unit of land tend to be located near urban centres. In this article it is tested to what extent these theoretical findings are confirmed by empirical data on agricultural land use and production for the EU-9. The focus is not only on the degree of concentration and specialisation, but also on their development over time. Growth and decline of agricultural productions are here related to the degree of rurality. It is found that high value productions indeed tend to be located in urban regions. It is also found that most specialisation patterns that already existed in 1950 are even stronger in 2000.